Chromatin Landscaping At Mitotic Exit Orchestrates Genome Function - Shoaib, Muhammad; Nair, Nidhi; Sørensen, Claus Storgaard (Frontiers in Genetics, 2020)
Chromatin architecture is highly dynamic during different phases of cell cycle to accommodate DNA-based processes. This is particularly obvious during mitotic exit, where highly condensed rod-like chromatids need to be rapidly decondensed. Such chromatin structural transitions are tightly controlled and organized as any perturbance in this dynamic process can lead to genome dysfunction which may culminate in loss of cellular fitness. However, the mechanisms underlying cell cycle-dependent chromatin structural changes are not fully understood. In this mini review, we highlight our current knowledge of chromatin structural organization, focusing on mitotic exit. In this regard, we examine how nuclear processes are orchestrated during chromatin unfolding and compartmentalization and discuss the critical importance of cell cycle-controlled chromatin landscaping in maintaining genome integrity.